1999
DOI: 10.1002/(sici)1099-0844(199906)17:2<107::aid-cbf815>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polydeoxyribonucleotides on human fibroblasts in primary culture

Abstract: The effects of a mixture of oligo- and polydeoxyribonucleotides (PDRN) on the growth and protein secretion of cultured human skin fibroblasts were investigated. Both intact and DNAase-digested PDRN stimulated cell proliferation to a similar extent. When cultured fibroblasts were incubated with radioactive amino acids in the presence of intact or digested PDRN the incorporation of the tracer into secreted proteins increased significantly. This stimulation appears to be specific for certain protein components, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(15 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In particular, although PDRN-treated cells showed low phosphate activity in the result of the sixth day compared to the control group, alkaline phosphatase activity was shown to gradually increase from the experiment starting day to the 10th day overall, and from these data, PDRN was proved to work as an osteoblast growth stimulant. Sini et al [6] investigated the effect of Oligo-composite and PDRN on growth and protein secretion of cultured human skin fibroblast and reported that both PDRN and DNAse-treated PDRN promoted the growth of cultured human fibroblast. Also, the cells cultured with PDRN were shown to promote the synthesis and secretion of protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, although PDRN-treated cells showed low phosphate activity in the result of the sixth day compared to the control group, alkaline phosphatase activity was shown to gradually increase from the experiment starting day to the 10th day overall, and from these data, PDRN was proved to work as an osteoblast growth stimulant. Sini et al [6] investigated the effect of Oligo-composite and PDRN on growth and protein secretion of cultured human skin fibroblast and reported that both PDRN and DNAse-treated PDRN promoted the growth of cultured human fibroblast. Also, the cells cultured with PDRN were shown to promote the synthesis and secretion of protein.…”
Section: Discussionmentioning
confidence: 99%
“…The implanted PDRN causes an angiogenesis phenomenon in neighboring soft tissue and induces [4, 5] new blood vessels to the implant site and differentiates [68] undifferentiated mesenchymal cells of the host into fibroblast and osteoblast, and then differentiated bone formation cells form new bones such as osteoid. Therefore, to investigate the quantitative level of bone-forming cells around DDM, the value derived from dividing the number of bone-forming cells around dentin particles by the number of dentin particles was expressed as a graph (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Purine nucleotides and nucleosides may be bound to receptors of a particular type and elicit different intracellular signaling pathways. They also have mitogenic effect on fibroblasts, endothelial cells, and neuroglia [ 38 , 39 ]. In addition, they synergize with a variety of growth factors [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…PDRN derivatives can boost nucleic acid synthesis via the salvage pathway [ 34 ] and/or by binding to purinergic receptors to respond to various stimuli such as hypoxia [ 33 , 35 ]. They can also act as growth promoters of fibroblasts [ 36 ], pelvis, ECs, and neuroglia [ 37 , 38 ]. This understanding inspires us to further investigate the effects of PDRN on IC-induced skeletal muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%